(3cja JcJH bUI ddCWaGd (B/s - (3GdQLHj, eMehO CHh aQhIs 1971- ((3YeGf (B- (3GdCQOf (B:s (3eDSSI GdaQSGf ddfTQ hGdJhRjY,s (3eDSSI JHGTjQ ddJOQjH hNOeGJ GdbUI hGdSjfGQjh,s, 2014)
(3jJfGhd GdcJGH SjfGQjh GdCWaGd GdehLhO aj eLdGJ GdCWaGd hGdSjfGQjh ef NdGd eSdSdGJ GdCWaGd GdEPGYjI hSjfGQjh GdCWaGd gh af eSJbd cdjG Yf GdbUI jJab eYgG aj HYV GdCTjGA dcfg jNJda aj CTjGA cKjQI hjMUd NdW cHjQ YfO HYV GdcJGH EP jNdWhf Hjf YfGUQ GdbUI hYfGUQ GdSjfGQjh eeG jDOj Edi VYag GdSjfGQjh hSjdI LejdI fSJWjY ef NdGdgG Cf fhUd GdbUI HWQjbI SdSI aHYV GdCWaGd dG jMHhf GdSQO hdcfge jMHhf GdUhQI hgj HYO LOjO jSGYO GdcGJH aj EjUGd eG jQjOg Edjge(B.s
(3hQO Ydi UaMI GdZdGa (B: (3SJ hKdGKhf NWhI aj GdWQjb fMh GdGMJQGa (B: (3ELGHGJ Ydi eGFI eTcdI ef eTcdGJ cJGHI GdbUI (B: (3CSdhH Ydej HSjW(B-(3eYRR HhSGFd dGSJfHGW YOO cHjQ ef CacGQ GdbUU GdLOjOI(B.s
(3JUeje hENQGL (B: (3efJUQ GdQLHj(B.s
Keywords: (3JbfjGJ GdJCdja hGdJMQjQs -- (3COH GdCWaGds -- (3cJGHI bUU GdCWaGds